Pengaruh Etika Kepemimpinan, Kompetensi SDM Dan Tingkat Pemahaman Akuntansi Terhadap Kualitas Laporan Keuangan BPR di Mengwi – Abiansemal Kabupaten Badung - I GUSTI NGURAH ADI SAPUTRA (Hita Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of the application of Effec Leadership ethic, humman resources competency and knewledge of accounting on the ouality of financial report at BPR of Mengwi-Abiansemal, Badung District. This research was conducted in all BPR of Mengwi-Abiansemal, Badung Dsitrict. Sampling method used porpusive random sampling with 21 BPR. Data collection with questionnaires with analysis technique used is multiple linear regression. The results show that leadership ethic have a positive significant effect on quality of financial report at BPR of Mengwi-Abiansemal, Badung Dsitrict, Humman resources competency have significant effect on quality of financial report at BPR of Mengwi-Abiansemal, Badung Dsitrict. Knewledge of accounting have a ssignificant effect on quality of financial report at BPR of Mengwi-Abiansemal, Badung Dsitrict.